Analisis Kelayakan Usaha Produksi Ayam Pedaging Berbasis Pangan Lokal dengan Variasi pada Kalsium dan Fosfor - Dira Asri Pramita; Charles Venirius Lisnahan; Alfred Nubatonis (Fakultas Pertanian, Universitas Timor, 2020)
This study aims to determine feasibility of broiler production based on local food with variations in calcium and phosphorus; and knowing difference feasibility of the business it gets. This research was conducted at farmer's cage in Sasi Village, Kefamenanu for 2 months (July-August, 2020). A total of 96 broiler day old chick (DOC) were used in this study. Research was conducted with an experimental method using a completely randomized design consisting of 4 treatments and 4 replications. Each replication consisted of 6 broiler chickens aged 1 day. Parameters observed were body weight, feed cost efficiency, sales price, and business feasibility. Data on body weight, feed cost and selling price of chickens were analyzed by Analysis of Variance (Anova) and Duncan's test, while business feasibility was analyzed by using B / C ratio. The results showed that the highest body weight, feed cost and selling price were found in P3. There is a feed cost efficiency at P3 and P2 compared to P1 and P0 (P <0.05), and highest revenue is at P3. Treatment with 2.0% calcium and 0.5% phosphorus (P3) supplementation be a highest economic feasibility. In addition, variation in treatment provides a significant difference in cost and selling value. Use of local feed of yellow maize and bran with calcium and phosphorus supplementation could reduce costs of broiler production.